The prospect of waste management system for solar power plants in Bangladesh : A case study - Ghosh, Mrittunjoy Kumar; Al Mansur, Ahmed; Aminul Islam Rifat, Md; Ali Mollik, Md Akbar; Ghosh, Anik Kumar; Soheb, Mohd; Islam, Md Imamul; Haq, Mohammad Asif ul (Institute of Electrical and Electronics Engineers Inc., 2023)
A possible path towards generating sustainable energy in Bangladesh is the use of solar power facilities. One crucial issue that necessitates attention is the effective handling of waste produced by these solar power facilities. Solar power plants are spreading across the country at an increasing rate as the need for renewable energy rises. While the focus primarily remains on the generation of clean energy, the management of waste, including photovoltaic module disposal must not be overlooked. The inappropriate treatment of waste from solar installations poses environmental and regulatory difficulties, and this article highlights the necessity for an all-encompassing waste management approach and how to recycle glass, aluminum, copper, silicon, and plastic considering the long-term benefits of reduced environmental impact and resource conservation. In this work, the prospect of a waste management system is analyzed for three solar power plants in Bangladesh. The plants are 28 MW Teknaf Solar Park, 73 MW Mymensingh Solar PV Park in Mymensingh, and 200 MW Teesta Solar Limited in Gaibandha. This work focuses on the recycled materials that can be obtained after the end-of-life of the plants. The results show that the amount of recoverable copper is 187.28 tonnes, aluminum is 1926.4 tonnes, silicon is 1018.82 tonnes, plastic is 1589.28 tonnes, and glass is 17744.44 tonnes from the proposed three PV power plants. Bangladesh can maximize the benefits of its solar power initiatives while minimizing environmental harm by confronting waste-related difficulties head-on and putting in place a successful waste management system.